Enhancing spin mastery in figure skating: A longitudinal case-control study on off-ice spin board training for rotational proficiency in young skaters - Drazdova, V. (Journal of Human Sport & Exercise, 2026)
Mastering fast and stable spins is a key challenge for young figure skaters. This study tested whether off-ice training using a spin board with gyroscopic feedback could improve spin performance in skaters aged 9 to 14. Over 36 months, we followed 40 skaters from Kazakhstan and Belarus. Half of the group used the spin board in addition to regular on-ice training, while the other half followed traditional training only. Skaters who used the spin board showed better results: faster rotation speeds (1,150 vs. 950 RPM; p < .001), earlier spin mastery (10.8 vs. 11.6 years; p = .04), and higher success rates in performance tests (78% vs. 62%; p = .002). Participants of this study self-reported feeling more confident during training and competition. In particular this paper includes a case study of the skater Mariya Sosnovskaya, who earned a top score of 101.89 points at a national event, demonstrating that the alternative training improved real-world performance. Our findings suggest that spin board training is a safe, practical, and effective way to help young athletes tremendously improve spin skills. Furthermore, it may also support confidence and reduce injury risks, making it a valuable tool for coaches and sports professionals.